Application of the Redlich-Kister expansion for estimating the density of molten fluoride psuedo-ternary salt systems of nuclear industry interest. (12th October 2022) - Birri, Anthony; Gallagher, Ryan; Agca, Can; McMurray, Jake; Dianne Bull Ezell, N.
Highlights: Several molten fluoride pseudo-ternary salt system densities were estimated. The estimation is based on Redlich-Kister expansion and Muggianu interpolation. This method generally outperforms estimation by additive molar volumes. Some unmeasured pseudo-binary system densities were also estimated. Abstract: The development of next-generation molten salt reactors relies on accurate knowledge of the thermophysical properties of the candidate coolant and fueled molten salts. These thermophysical properties include density, viscosity, thermal conductivity, and heat capacity. Because of difficulties in measuring thermophysical properties of molten salts, there are many gaps in the current state of thermophysical property knowledge of these salts, particularly those that contain actinides or beryllium. Therefore, leveraging modeling techniques to estimate unknown molten salt thermophysical properties and guide future experimental measurements has high value for the nuclear industry. In this study, the densities of molten fluoride pseudo-ternary salt systems, which are of interest to the nuclear industry, were estimated using Redlich-Kister expansion and Muggianu interpolation techniques. The pseudo-ternary systems considered for estimation in this study were NaF-LiF-ZrF4, LiF-BeF2 -ZrF4, LiF-BeF2 -ThF4, NaF-LiF-BeF2, NaF-KF-BeF2, NaF-ZrF4 -UF4, and NaF-BeF2 -UF4 . This Redlich-Kister estimation approach accounts for nonideal mixing behavior based on pseudo-binary subsystem interaction parameters determined from experimentally measured pseudo-binary system density data sets. The Redlich-Kister estimation was compared with the method of additive molar volumes, which assumes ideal mixing. The Redlich-Kister approach was also used to determine previously unknown binary and ternary interaction parameters based on experimentally measured density data sets for select pseudo-ternary salt systems. The results of this study show improvement in density estimation using the Redlich-Kister approach for all systems considered compared with estimation by additive molar volumes. Furthermore, this analysis allowed for the estimation of nonideal density behavior in experimentally unstudied ZrF4 -UF4 and BeF2 -UF4, as well as the quantification of ternary interaction in NaF-LiF-ZrF4, NaF-BeF2 -UF4, and NaF-ZrF4 -UF4 .